Execution and challenges of using focus group discussions as a research tool for secondary school students - Vidyadaran, Sharmili; Abdullah, Maha; Gyanchand Rampal, Lekhraj Rampal; Mohd Tohit, Eusni Rahayu; Kandiah, Mirnalini; Khor, Geok Lin; Mohtarrudin, Norhafizah; Leong, Joyce Whye Sook; Choo, Beng Huat; Ramasamy, Rajesh; Mohan Singh, Avatar Singh; Chan, Yoke Mun; et al. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Focus group discussions (FGD) are a valuable method to obtain information and explore attitudes, feelings and views on a subject of research, especially when existing knowledge of the subject is inadequate. We used FGD as a tool to develop a cardiovascular disease (CVD) behavioural intervention programme for secondary school students. In this paper, we describe the planning and execution of the FGD and the various challenges faced. We believe that FGD will lead to development of a suitable and relevant intervention programme for our target group. Methods: Four out of nine districts in Selangor state were selected at random using the table of random numbers. In each of the selected districts, three schools were selected at random from the total list of schools. Participants to the FGD included students, teachers, parents and canteen operators who were then selected from the schools based on a voluntary basis of participation. Twenty-one facilitators and 20 scribes were trained to conduct the FGD. Questions for the FGD were semi-structured around six themes: CVD and its risk factors; diet; physical activity; self-image; smoking; and miscellaneous. Training for facilitators was provided using a Facilitator's Guide. Results: A total of 33 focus group discussions were conducted involving 297 participants from 11 schools. Discussions were scribed, audio taped and transcribed. Incentives for transport, certificates of participation and favourable venue were important motivating factors for participation. Conclusion: Detailed planning is important for the successful implementation of a FGD. An adequately planned and well-managed FGD can serve as an important tool to explore views of a research target population and develop a CVD behavioural intervention programme.